PROFIL USAHA KLAPERTAART MANADO - Crystalinda T. O. Mekel; Jenny ., Baroleh; Caroline B. D. Pakasi (Sam Ratulangi University, 2015)
This study aims to provide a description of the Petra klapertaart business in terms of raw materials, capital, labor, production, costs, and the amount of profit earned.This research was conducted for one mounth on October 2015. The data used are primary data get from the owner. Petra klapertaart is one of the home industries that can give value added to coconut plants, particularly coconuts, so it can help coconut farmers to improve their economy. Constraints limited capital to run the business, get solution from the Ministry of Agriculture that is Petra klapertaart registered as one of a member the Independent Institute Rooted in the Community (LM3), which receive capital assistance in the form of funds. This led to make a research to see the description of the business profile Petra klapertaart after getting financial aid from the Ministry of Agriculture. Data obtained with primary data taken by researchers from business owners as the the main source. Data collection techniques were done by direct observation and interviews with business owners.Â The results showed that the Petra klapertaart business is a small-scale business that uses coconut raw materials that processed into klapertaart and became one of the members of the Independent Institute Rooted in the Community (LM3) which get funding. On Klapertaart marketing activities, business owners deal directly with consumers to sell klapertaart. Based on the results, the amount of production, the amount of production in September 2015, which is 12 times the production made two recipes in each production, produce 348 klapertaart cup aluminum foil, make a profit with the ratio of R / C> 1 is equal to 1.84 in September 2015 means, Petra business get the benefits, so this business is effort to develop